1999
DOI: 10.3354/meps188299
|View full text |Cite
|
Sign up to set email alerts
|

Species composition and inshore migration of the tropical eels Anguillaspp. recruiting to the estuary of the Poigar River, Sulawesi Island

Abstract: In order to determine the species composition and inshore migration of the tropical eels Anguilla spp. migrating to an Indonesian river, we collected 21 633 glass eels at the mouth of the Poigar River, north Sulawesi Island, throughout 1997, and subjected these samples to both morphological examination and polymerase chain reactionrestriction fragment length polyrnorphism (PCR-RFLP) analysis. Three species, Anguilla celebesensis, A. marmorata and A. bicolorpacifica, were found throughout the season in fluctuat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 7 publications
1
58
0
2
Order By: Relevance
“…Present data on the 4 Indian eels from literature and from present study 2001a). According to available data, insular recruitment of A. marmorata occurs throughout the year in its Pacific distribution area (Marquet & Lamarque 1986, Marquet 1987, Arai et al 1999b, with different seasonal peaks occurring locally in response to regional hydroclimatic conditions. In Indonesia and the Philippines, A. marmorata recruitment peaks in February to March (Tabeta et al 1976, Budimawan 1997, Arai et al 2002, while in French Polynesia 2 annual peaks occur, 1 in January to February and 1 in March to April (Marquet 1992).…”
Section: Recruitment Patternsmentioning
confidence: 99%
“…Present data on the 4 Indian eels from literature and from present study 2001a). According to available data, insular recruitment of A. marmorata occurs throughout the year in its Pacific distribution area (Marquet & Lamarque 1986, Marquet 1987, Arai et al 1999b, with different seasonal peaks occurring locally in response to regional hydroclimatic conditions. In Indonesia and the Philippines, A. marmorata recruitment peaks in February to March (Tabeta et al 1976, Budimawan 1997, Arai et al 2002, while in French Polynesia 2 annual peaks occur, 1 in January to February and 1 in March to April (Marquet 1992).…”
Section: Recruitment Patternsmentioning
confidence: 99%
“…Total length, predorsal, preanal and ano-dorsal lengths of each specimen were measured to the nearest 0.1 mm, and pigmentation stages were determined according to Bertin (1956). All specimens were identified morphologically (Ege 1939, Tabeta et al 1976 and genetically (Arai et al 1999a).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the 3 tropical species studied here have been found to recruit into freshwater at the Poigar River, Sulawesi Island, Indonesia (Fig. 1), throughout the year in varying abundances, indicating almost year-round spawning for A. marmorata and A. celebesensis (Arai et al 1999a). The greatest abundance of A. marmorata and A. celebesensis during recruitment was in June, but that of A. bicolor pacifica was much more sporadic.…”
Section: Life History Implicationsmentioning
confidence: 99%
“…Of the latter, 7 species/subspecies occur in the western Pacific around Indonesia: A. celebesensis, A. interioris, A. nebulosa nebulosa, A. marmorata, A. borneensis, A. bicolor bicolor and A. bicolor pacifica (Ege 1939, Castle & Williamson 1974, Arai et al 1999a). Recent mitochondrial DNA analysis has revealed that A. borneensis from Borneo Island is closest to the ancestral form among the 15 presently known species .…”
Section: Introductionmentioning
confidence: 99%